Triple (GGTA1, CMAH, B2M) modified pigs expressing an SLA class Ilow phenotype—Effects on immune status and susceptibility to human immune responses. Issue 4 (28th December 2019) - Hein, Rabea; Sake, Hendrik J.; Pokoyski, Claudia; Hundrieser, Joachim; Brinkmann, Antje; Baars, Wiebke; Nowak‐Imialek, Monika; Lucas‐Hahn, Andrea; Figueiredo, Constanca; Schuberth, Hans‐Joachim; Niemann, Heiner; Petersen, Björn; et al.
Abstract : Porcine xenografts lacking swine leukocyte antigen (SLA) class I are thought to be protected from human T cell responses. We have previously shown that SLA class I deficiency can be achieved in pigs by CRISPR/Cas9‐mediated deletion of β2 ‐microglobulin (B2M). Here, we characterized another line of genetically modified pigs in which targeting of the B2M locus did not result in complete absence of B2M and SLA class I but rather in significantly reduced expression levels of both molecules. Residual SLA class I was functionally inert, because no proper differentiation of the CD8 + T cell subset was observed in B2M low pigs. Cells from B2M low pigs were less capable in triggering proliferation of human peripheral blood mononuclear cells in vitro, which was mainly due to the nonresponsiveness of CD8 + T cells. Nevertheless, cytotoxic effector cells developing from unaffected cell populations (eg, CD4 + T cells, natural killer cells) lysed targets from both SLA class I + wildtype and SLA class I low pigs with similar efficiency. These data indicate that the absence of SLA class I is an effective approach to prevent the activation of human CD8 + T cells during the induction phase of an anti‐xenograft response. However, cytotoxic activity of cells during the effector phase cannot be controlled by this approach. Abstract : Cells from genetically engineered pigs expressing an SLA class Ilow phenotype do not trigger in vitro proliferation of human CD8+ T cells but are susceptible to cellular cytotoxicity.